Proceedings of the International Conferences on Educational, Social Sciences and Technology - ICESST 2018 2018
DOI: 10.29210/20181137
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of reading interest on literature and reading comprehension toward students’ ability in writing fantasy story

Abstract: The purpose of this research was to figure out the contribution of reading interest on literature and reading comprehension toward students' ability in writing fantasy story of VII grade of junior high schools in Padang. This research was quantitative research that applied correlational method. The sample were 106 students. The sampling technique was stratified random sampling. Data were analyzed by using Pearson Product Moment Correlational test, multiple regression, t test, and F test. The result shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Participants' interest in reading using webtoon can be concluded that reading interest for activities carried out continuously can form communication patterns with oneself and can develop participant intellectuality generated through writing, how to solve participant problems and good communication. This is supported theory from Suhendar stated that interest is one of the important factors affecting reading ability (as cited in Endah et al, 2018) so that interest can be used as a strong encouragement to increase reading literacy.…”
Section: Interest In Using Webtoonsupporting
confidence: 58%
“…Participants' interest in reading using webtoon can be concluded that reading interest for activities carried out continuously can form communication patterns with oneself and can develop participant intellectuality generated through writing, how to solve participant problems and good communication. This is supported theory from Suhendar stated that interest is one of the important factors affecting reading ability (as cited in Endah et al, 2018) so that interest can be used as a strong encouragement to increase reading literacy.…”
Section: Interest In Using Webtoonsupporting
confidence: 58%
“…This was because it would more likely allow them to develop their inspiration and imagination to make a text. Using a less suitable model might affect negatively students' ability to obtain inspiration (Endah et al, 2018;Egan, 2001;Knoeller, 2003;. Therefore, this ethnoliteracy-based guided discovery learning model was highly suitable for students in imaginary story writing course as could be seen from teachers' and students' responses while the study was being conducted.…”
Section: Development Trialmentioning
confidence: 99%
“…Therefore, more intensive facilitation is needed in the process of writing imaginary stories for students to make their writings more guided towards a storytelling. It is quite frequent that the difficulty in writing imaginary stories comes from the use of a less effective learning model, preventing students from obtaining adequate inspiration to write a prose (Endah et al, 2018;Egan, 2001;Knoeller, 2003;. Based on Listiani's (2020) research, the learning model that includes field observation is the one that most students want.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the preliminary study, information was obtained that the students' narrative essay writing skills were still not optimal. That is because the students' low interest in reading affects the students' understanding (Endah, Effendi Thahar, & Asri, 2018). Moreover, students also do not recognize the surrounding environment well.…”
Section: Introductionmentioning
confidence: 99%